(3MGTjI Ydi GdTeSjIs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3jbhd eMeO Hf GSYO GdOhGfi GdUOjbi cKjQG eG CdM Ydi ENhGfi Cf CLeY dge TQM GdTeSjI s
(3BNQgG (B:s
(3JeJ s
(3Vef eLehY , JQJjHgG (B: 5s
(3GdQSGdI GdCUdjI(B: (3GdQSGdI GdTeSjI ai GdbhGYO GdefWbjI ddcGJHis
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
Keywords: (3GdadSaI hGdefWbs